2019
DOI: 10.1039/c8ra09899a
|View full text |Cite
|
Sign up to set email alerts
|

Intact mangrove root electrodes for desalination

Abstract: Biological adaptation in mangrove root enables freestanding carbonized architecture to be used as a highly permeable flow-through capacitive deionization electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The salt concentration of the solution exiting the FT-CDI cell was measured using a custom-built conductivity meter which is described in detail in Wood et al 2019. 29 The salt adsorbed was calculated by quantifying the area between the stock solution (1200 mg L −1 ) and the permeate solution during the charging phase of the CDI cycle. The SAC was calculated by dividing the salt adsorbed by the net mass of the electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The salt concentration of the solution exiting the FT-CDI cell was measured using a custom-built conductivity meter which is described in detail in Wood et al 2019. 29 The salt adsorbed was calculated by quantifying the area between the stock solution (1200 mg L −1 ) and the permeate solution during the charging phase of the CDI cycle. The SAC was calculated by dividing the salt adsorbed by the net mass of the electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…The SAC is dened as the ratio of salt adsorbed from the feed stream to the mass of the electrode pair. 47 Values for SAC typically range from 2 mg g À1 to as high as 21 mg g À1 for FT electrodes and naturallybased electrodes, 29 although other studies have also reported lower values. 14 L is the ratio of salt adsorption to charge transferred and is indicative of energy consumption.…”
Section: Performance Characterization Of Bread-derived Electrodes In mentioning
confidence: 99%
See 1 more Smart Citation